Air emissions measurements at cattle feedlots - Baum, Kristen A. (Kansas State University, 2008)
The potential environmental impact of animal feeding operations on air quality has created the need for accurate air emissions measurements. Of particular concern are ammonia emissions from cattle feedlots, operations that contribute a large portion of the agricultural ammonia emissions inventory. Micrometeorological methods are ideal for emissions measurements from large, open-source areas like feedlot pens; however, theoretical assumptions about the boundary layer must be made, which may not hold true above the heterogeneous, fetch-limited surface of the feedlot. Thus, the first objective of this work was to characterize the surface boundary layer of an open-air cattle feedlot and provide insight into how micrometeorological techniques might be applied to these non-ideal sites. Eddy covariance was used to measure fluxes of momentum, heat, water, and carbon dioxide from a commercial cattle feedlot in central Kansas. Data supported the use of eddy covariance and similar methods (i.e., relaxed eddy accumulation) for flux measurements from both cattle and pen surfaces. The modeled cumulative source area contributing to eddy covariance measurements at a 6 m sample height was dominated by just a few pens near the tower, making the characteristics of those pens especially important when interpreting results. The second objective was to develop a system for measuring ammonia fluxes from feedlots. A new type of relaxed eddy accumulation system was designed, fabricated, and tested that used honeycomb denuders to independently sample ammonia in up-moving and down-moving eddies. Field testing of the relaxed eddy accumulation system at a feedlot near Manhattan, KS showed fluxes of ammonia ranged between 60 and 130 μg m-2 s-1 during the summer of 2007. Even in the high ammonia environment (e.g., 300-600 μg m-3), the honeycomb denuders had enough capacity for the 4-hour sampling duration and could be used to measure other chemical species that the denuders could be configured to capture. Results provide a foundation for emissions measurements of ammonia and other gases at cattle feedlots and help address some of the challenges that micrometeorologists face with any non-ideal source area.
Keywords: Air emissions measurements; Confined Animal Feeding Operation; Cattle feedlot; Ammonia; Eddy Covariance; Relaxed Eddy Accumulation; Agriculture, Agronomy (0285); Engineering, Agricultural (0539)